Deuterated water (2H2O, heavy water) labelling to investigate human cell dynamics in vivo - lessons in protocol design and toxicity from the current literature - Song, Ami; Zhang, Yan; Busch, Robert; Asquith, Becca; Macallan, Derek (Frontiers in Immunology, 2025)
The use of deuterated water (also known as ‘heavy water’) as a tracer to measure human in vivo cell proliferation rates for specific cell subsets has expanded significantly in recent years. Although there have been several published methods papers, investigators developing new applications may be confused by differences in study design and deuterated water dose/duration. Furthermore, this approach may be met with regulatory difficulties and participant concerns about toxicity. This scoping review explores lessons that can be learnt from the current literature on the use of deuterated water in human in vivo studies measuring cell proliferation. We identified 29 such studies involving 535 study participants, both healthy volunteers and those with specific clinical conditions. Wide variations in protocols were noted with doses ranging from 40-100 ml/day of pure deuterated water (or equivalent) and durations from 4-12 weeks. Study design usually reflected the kinetics of the cell of interest. No clinical toxicity signals were noted in any studies although four studies did report transient dizziness, a recognized symptom of changing water density. These published studies provide a strong safety signal for potential participants and regulatory authorities and can act as templates for the development of new research applications.